Administrasi Publik, Program Pascasarjana Universitas Pattimura - Rumfot, Jalil (Patria Artha Management Journal, 2023)
This study aims to analyze the Management Strategy of MiratiDewaningsihTuasikal in the Implementation of the Functions of the Regional People's Representative Council of the Republic of Indonesia (DPD-RI) in Ambon City. The data collection technique used was an in-depth interview with the help of an interview guide. Document tracing is carried out directly while observing, reading, understanding concepts, to obtain secondary data on work reports, statutory regulations, decrees, and brochures related to the problem at hand. The data from this study were analyzed using descriptive qualitative analysis techniques. The results of the study show that, MiratiDewaningsihTuasikal's Management Strategy in the Implementation of the RI DPD Functions in Ambon City which includes aspects of: a) planning (planing), b) organizing (organizing), c) implementation (actuating), and d) monitoring (controlling) ) went well where it was able to meet public expectations.